1949
DOI: 10.1007/bf02634831
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic equilibrium of peanuts

Abstract: Summary and Conclusions The hygroscopic equilibria and rates of attainment of hygroscopic equilibrium of freshly dug, naturally cured, and artificially cured peanuts have been determined over the range of 11–93% relative humidity at 25°C. The hygroscopic equilibrium does not appear to be dependent on the method of curing. At a constant relative humidity, the moisture content is distributed so that the moisture content of the skins is twice that of the meats and in general the moisture content is lowest in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1950
1950
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Peanuts were preconditioned to moisture contents of5, 7, and 8% in rooms maintained at proper conditions to achieve the desired moisture content as described by Karon and Hillery (1949). The time for peanuts to achieve the desired moisture content levels varied from 28 to 35 days.…”
Section: Laboratory Testmentioning
confidence: 99%
“…Peanuts were preconditioned to moisture contents of5, 7, and 8% in rooms maintained at proper conditions to achieve the desired moisture content as described by Karon and Hillery (1949). The time for peanuts to achieve the desired moisture content levels varied from 28 to 35 days.…”
Section: Laboratory Testmentioning
confidence: 99%
“…Blue lupine seeds seem to attain equilibrium with humidity of the air more slowly than do many other seeds and grains for which results have been reported (4,9,10,11,12,15). This slower rate of absorption of moisture in the vapor phase is coupled, however, with a higher total uptake than is found in many other seeds.…”
Section: Discussionmentioning
confidence: 80%
“…These seeds showed a slight mold growth, and their relatively high moisture content was no doubt partly attributable to a decrease in seed dry matter due to fungal metabolism or to moisture held by the fungus mycelium itself. Workers using other seeds (4,9,10,11,12,15) figure 2 (B, C) was designed to show the differences between the 6-week and 8-week storage periods in effects on seed-air moisture exchanges throughout the relative humidity range. From the preliminary studies and from these data, it was concluded that naturally dried blue lupine seed apparently requires seven to eight weeks to attain equilibrium with air of high and low relative humidities but not more than six weeks with air of intermediate humidities.…”
Section: Brewer and Butt: Blue Lupine Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. Experimental data for water sorption in rice at different temperatures (°C) (a) Abdullah et al (2000), Banaszek and Siebenmorgen (1990), Breese (1955), Juliano (1964), Putranon et al (1979), Rangaswamy (1973) and desorption (b) Bakharev (1960), Breese (1955), Coleman and Fellows (1925), Hogan and Karon (1955), Houston (1952), Humphries and Hurst (1935), Juliano (1964), Kachru and Matthes (1976), Kameoka et al (1988), Karel et al (1955), Karon and Adams (1949), Putranon et al (1979), Rangaswamy (1973), Vemuganti (1980), and Zuritz et al (1979).…”
Section: Rice and Potatoesmentioning
confidence: 97%